Simultaneous resection of left atrial myxoma and cardiac revascularization - Ostrowski, Stanisław; Wrona, Ewa; Kośmider, Anna; Zwoliński, Radosław; Marcinkiewicz, Anna; Walczak, Andrzej; Miśkowiec, Dawid; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Introduction : Cardiac myxomas are extremely rare entities, usually localized in the left atrium. They require surgical intervention, which can give very good results and minimal risk of recurrence. The procedure, as well as the patient’s condition, is complicated by comorbidities such as advanced coronary disease which requires revascularization. Case Description : An 82-year old woman was admitted to the Emergency Department with symptoms of palpitations and dyspnoea. Electrocardiography (ECG), transthoracic echocardiography (TTE) and coronary angiography were performed during the diagnostic procedure. Left atrial tumour was diagnosed, whose appearance suggested cardiac myxoma, as well as significant stenosis of the left anterior descending artery (LAD) that required revascularization. It was decided that a venous bypass should be performed with tumour resection during a single procedure. During convalescence of the patient, respiratory and circulatory complications occurred. After three weeks of hospitalization, the woman was released from hospital in good condition. Conclusion : This is the first patient who was qualified for surgical treatment of a cardiac myxoma and revascularization at the same time in our clinic.